PROFIL KEMAMPUAN LITERASI NUMERASI DAN LITERASI BUDAYA SISWA KELAS VII SMP NEGERI DI KECAMATAN PALU SELATAN - Suciati, Indah; Tangge, Lilies N.; Afadil, Afadil (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2024)
Qualitative descriptive research was conducted to see the profile of the numeracy literacy and cultural literacy abilities of class VII students at State Middle Schools in South Palu District. By using purposive random sampling, 68 students were selected at SMP Negeri 6 Palu and SMP Negeri 21 Palu. The instruments used were a 5-number numeracy literacy ability assessment test in multiple choice form and a 20-number cultural literacy ability assessment test in the form of reasoned choices. The data analysis used refers to the Miles & Huberman analysis which consists of data collection, data reduction, presentation, and conclusion. The results show that the numeracy literacy skills of class VII students at State Middle Schools in the South Palu sub-district are in the low category. Likewise, cultural literacy skills are in the low category. Therefore, it is hoped that teachers and policymakers can develop more effective and inclusive learning strategies, such as learning processes that emphasize literacy but are linked to cultural elements, as adequate learning facilities such as books and learning materials that focus on numeracy and cultural literacy. There is also a need for involvement from parents and the community to help students become more familiar with their regional culture so that cultural identity is maintained